Pengaruh Latihan Mobilisasi Saraf Terhadap Penurunan Nyeri Pada Penderita Carpal Tunnel Syndrome Di Poli Fisioterapi RSUD Meuraxa Banda Aceh - Anna Anna; Wahyu Wijanarko; Ida Aryani Pasaribu (LPPM STIKES Siti Hajar dan Insight Power, 2023)
Background : Carpal tunnel syndrome is a disorder characterized by tingling and pain in the hands and fingers due to damage to the median nerve. The pain may radiate to the arm to the elbow, although it rarely radiates to the elbow. Carpal tunnel syndrome is one of the disorders of the forearm due to narrowing of the carpal tunnel, either due to fascial edema in the tunnel or due to abnormalities in the small bones of the hand resulting in compression of the median nerve at the wrist. Carpal tunnel syndrome involves the median nerve which is prone to compression and injury in the palm and wrist, where it is bounded by the wrist bone and the transverse carpal ligament. To reduce pain in carpal tunnel syndrome, nerve mobilization exercises are given with sliding and tensioner movements. Methods : This research is a quasi-experimental with the research design used in this study is a one group pretest-posttest design, using the Visual Analogue Scale (VAS) measuring instrument. The population in this study were all patients with carpal tunnel syndrome. Sampling was carried out by the total sampling method, namely the entire population obtained was used as a research sample of 27 patients. Results : the normality test with Shapiro-Wilk showed that the data were not normally distributed. The technique used to analyze the data is the non-parametric test, namely Wilcoxon with a value of p = 0.000 (p = <0.05) so that H0 is rejected. Ha is accepted. Conclusion : There is an effect of nerve mobilization exercise on the reduction in patients with Carpal Tunnel syndrome at the Physiotherapy Poly at Meuraxa Hospital Banda Aceh. Keywords: Exercise, Nerve Mobilization, Carpal Tunnel Syndrome.